2011
DOI: 10.1108/20420921111207873
|View full text |Cite
|
Sign up to set email alerts
|

Deaths in custody: the role of restraint

Abstract: PurposeThe practice of restraint is controversial as deaths in care or custody have been a consequence of restraint. The purpose of this paper is to clarify research from national and international literature to ascertain any common findings in order to provide guidance for staff on safe and effective restraint techniques where there is no other resort in the management of violent and aggressive individuals.Design/methodology/approachThe researchers undertook a review of the literature on the medical theories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…, Ashcraft & Anthony , Duxbury et al . ). Further, physical injuries ranging from those that are minor to major, have been reported, including coma, broken bones, bruises, cuts requiring stitches, facial damage, dehydration, choking, circulatory and skin problems, loss of mobility, and incontinence (Paterson & Duxbury ).…”
Section: Discussionmentioning
confidence: 97%
“…, Ashcraft & Anthony , Duxbury et al . ). Further, physical injuries ranging from those that are minor to major, have been reported, including coma, broken bones, bruises, cuts requiring stitches, facial damage, dehydration, choking, circulatory and skin problems, loss of mobility, and incontinence (Paterson & Duxbury ).…”
Section: Discussionmentioning
confidence: 97%
“…Coercion has been shown to be harmful for both service users and staff within mental health care, being injurious, traumatizing and re‐traumatizing, making the case for trauma‐informed care (Department of Health, ; Duxbury, Aiken, & Dale, ; MIND, ; Muir‐Cochrane, ; Sweeney, Filson, Kennedy, Collinson, & Gillard, ). Concomitantly, there has been widespread international interest in nurse staffing levels, across healthcare contexts, including mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The panel commissioned Duxbury et al. () to conduct a systematic review of the most up to date national and international research on restraint‐related deaths. The report authors concluded, “There is much rhetoric and advice given in the press and professional journals on preventing restraint‐related deaths but much of this is based on opinion and less on valid studies.…”
Section: Time and The Multifactorial Causes Of Restraint Deathmentioning
confidence: 99%
“…It is now generally accepted that the risk of death arising from restraint is not exclusively linked to specific techniques, nor wholly attributable to certain positions (Paterson et al., ). Rather, the fatal outcome is determined by a combination of the prevailing health status of the individual being restrained, the physiological changes caused by the subjective experience of restraint along with the resulting resistance to it, as well as the nature and degree of force employed by staff (Duxbury, Aiken, & Dale, ). The research base around our understanding of these risk factors and their interplay continues to grow despite real‐world fidelity within experiments often remaining ethically out of reach (Paterson et al., ; Tamsen & Thiblin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation